PERSEPSI GURU MATEMATIKA TERHADAP PEMBELAJARAN SECARA DARING SELAMA MASA PANDEMI COVID-19: PELUANG DAN TANTANGAN - Yovika Sukma; Nanang Priatna (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
The Indonesian government made several policies to reduce the coronavirus spread, including in the education sector, by implementing online learning from home. This study aims to determine the mathematics teachers' perception of online learning implementation during COVID-19 related to its challenges and opportunities. The method used in this study was an exploratory method in which the researchers used the questionnaire to gather the information. A total of 65 mathematics teachers from various education levels around South Sumatra, Indonesia, became the respondents. Based on the analysis of 65 mathematics teachers' responses, more than half of the respondents used the WhatsApp platform to carry out online learning activities. In implementing online learning, there were some challenges faced by mathematics teachers, such as students who did not have the facilities required for online learning. Although teachers still faced challenges, the teacher stated that online learning provided opportunities for teachers to upgrade themselves and learn more about educational technology. Moreover, online learning provided opportunities for students to communicate with other students and teachers alike unlimited by time. This study could provide an overview and information related to challenges and opportunities in implementing online learning for mathematics, which can be used in online learning activities during the COVID-19 pandemic.